Evaluating Quantitative Reasoning Strategies for Comparing Fractions: A Tool for Teachers. (March 2019) - Crawford, Lindy; Quebec Fuentes, Sarah; Huscroft-D'Angelo, Jacqueline; Higgins, Kristina N.
Meaningful inclusion of quantitative reasoning into mathematics instruction requires meaningful ways to evaluate it. Few formative assessments exist to evaluate the strategies students use when reasoning mathematically. The Framework for Evaluating Quantitative Reasoning Strategies presented in this article provides teachers with categories for evaluating types of quantitative reasoning strategies students use for problems in the mathematical domain of number and operations. Numerous examples of the types of strategies students use for comparing fractions and how to evaluate the complexity of these strategies are provided. Included are research-based instructional recommendations for moving students toward a deeper conceptual understanding of fractions as numbers.